The implication of economic factors on foreign direct investment in Singapore / Christina Anak Dana - Anak Dana, Christina (Faculty of Business Management, 2017)
This research to determine the implication of economic factors on foreign direct investment (FDI) in Singapore for the period 1996 until 2015. The findings using method Multiple Linear Regression Model, Autocorrelation, T-test and F-test, Unit root test , and Normality test. Research paper is focus on economic factors such as gross domestic product (GDP), inflation rate (CPI), government final consumption (GFC), export and import in Singapore.